Contributions to advances in blend pellet products (BPP) research on molecular structure and molecular nutrition interaction by advanced synchrotron and globar molecular (Micro)spectroscopy. Issue 16 (8th September 2019) - Guevara-Oquendo, Víctor H.; Zhang, Huihua; Yu, Peiqiang
ABSTRACT: To date, advanced synchrotron-based and globar-sourced techniques are almost unknown to food and feed scientists. There has been little application of these advanced techniques to study blend pellet products at a molecular level. This article aims to provide recent research on advanced synchrotron and globar vibrational molecular spectroscopy contributions to advances in blend pellet products research on molecular structure and molecular nutrition interaction. How processing induced molecular structure changes in relation to nutrient availability and utilization of the blend pellet products. The study reviews Utilization of co-product components for blend pellet product in North America; Utilization and benefits of inclusion of pulse screenings; Utilization of additives in blend pellet products; Application of pellet processing in blend pellet products; Conventional evaluation techniques and methods for blend pellet products. The study focus on recent applications of cutting-edge vibrational molecular spectroscopy for molecular structure and molecular structure association with nutrient utilization in blend pellet products. The information described in this article gives better insight on how advanced molecular (micro)spectroscopy contributions to advances in blend pellet products research on molecular structure and molecular nutrition interaction.